Islamic Criminal Law Against Crypto Fraudsters: Between Ta'zir and Sharia Fintech Regulations - Liantha Adam Nasution; Syahril Fatihul Ihsan; Siti Aminah (El-Sirry: Jurnal Hukum Islam dan Sosial, 2026)
The development of digital technology has given birth to various new forms of financial transactions, one of which is cryptocurrency or crypto assets. In Indonesia, the number of crypto asset investors has increased from around 18.8 million people at the beginning of 2024 to more than 21.6 million people by the end of 2024, with an annual transaction value that grows hundreds of percent, but this growth is also followed by the rise of fraud under the guise of crypto investment such as trading robots, ponzi schemes, and phishing that harm people economically and psychologically. This study aims to analyze how Islamic criminal law views crypto fraud perpetrators, identify the elements of jarimah in it, and examine the extent to which sharia fintech regulations in Indonesia are able to provide legal protection for the public. The research uses a qualitative method with a normative approach and literature study through the analysis of empirical data from Bappebti/OJK, crypto fraud cases in Indonesia and internationally, DSN-MUI fatwas, positive regulations, and contemporary Islamic legal literature. The results of the study show that crypto fraud meets the elements of gharar, tadlis, and akl al-māl bi al-bāṭil so that it is categorized as jarimah ta'zir whose sanctions need to be operationalized based on the level of loss and social impact. Sharia fintech regulations in Indonesia, including the transfer of supervision from Bappebti to the Financial Services Authority (OJK) through POJK Number 27 of 2024, still face obstacles in coordination between institutions and limited protection for victims of illegal platforms. The integration of positive law, institutional strengthening, digital literacy and sharia finance, and the principles of maqāṣid sharia is the key in dealing with the development of digital financial crimes in the modern era.